SCIENTIFIC AND THEORETICAL BASIS OF FACTORS FOR IMPROVING FAMILY EDUCATION IN A MULTILINGUAL ENVIRONMENT - Mamaraimova Zebo Shafoatovna (Scholar Express Journals, 2021)
Multilingualism is the ability of an individual speaker or a community of speakers to communicate effectively in three or more languages. Contrast with monolingualism, the ability to use only one language. A person who can speak multiple languages is known as a polyglot or a multilingual. The original language a person grows up speaking is known as their first language or mother tongue. Someone who is raised speaking two first languages or mother tongues is called a simultaneous bilingual. If they learn a second language later, they are called a sequential bilingual
Keywords: Family and family business, family business, small